Discovery of 2-vinyl-10H-phenothiazine derivatives as a class of ferroptosis inhibitors with minimal human Ether-a-go-go related gene (hERG) activity for the treatment of DOX-induced cardiomyopathy. (15th October 2022) - You, Jing; Yang, Wei; Ma, Ronggang; Xia, Anjie; Zhang, Guo; Fang, Zhen; Guo, Nihong; Yang, Shengyong; Li, Linli
Graphical abstract: Abstract: Ferroptosis was an iron-dependent, nonapoptotic form of regulated cell death. In our previous study, we discovered a potent ferroptosis inhibitor with phenothiazine scaffold (1 ), but subsequent investigation showed that this compound had potent hERG binding affinity. Herein, we report the discovery of a series of 2-vinyl-10 H -phenothiazine derivatives as new class of ferroptosis inhibitors. Structure-activity relationship (SAR) analyses led to the identification of compound 7j, which exhibited significantly reduced hERG inhibition (IC50 > 30 µM) while maintaining high ferroptosis inhibitory activity (EC50 = 0.001 µM on the erastin-induced HT1080 cell ferroptosis model). Further studies confirmed 7j acted as a ROS scavenger and could relieve DOX-induced cardiomyopathy. 7j also displayed favorable pharmacokinetic properties and exhibited no obvious toxicity in vivo and vitro . Overall, this study provides a promising lead compound for drug discovery targeting ferroptosis.